33 Characteristics of patients undergoing pre-hospital rapid sequence intubation by intensive care flight paramedics in victoria, australia. (21st May 2017) - Delorenzo, A; Clair, St T; Andrew, E; Bernard, S; Smith, K
Abstract : Aim: Rapid sequence intubation (RSI) is an advanced airway procedure for critically ill or injured patients. The role of RSI in the pre-hospital setting, and who should perform the procedure remains controversial. In Victoria, Intensive Care Flight Paramedics (ICFPs) have a broad scope of practice for RSI, including high Glasgow Coma Score (≥10). We sought to describe the success rates and characteristics of patients receiving RSI by highly trained ICFPs in Victoria, Australia. Methods: A retrospective data review was conducted of adult (≥16 years) patients who received RSI by an ICFP between the 1st January 2011 and 31st December 2016. Data were sourced from the Ambulance Victoria data warehouse. Patients<16 years of age and physician retrieval cases were excluded. Results: A total of 777 cases were included in analyses with a mean age of 45 years (SD 19.6). Most patients were male (69.5%) and the majority of cases involved trauma (72.3%). The overall success rate of intubation was 99.4%. Of the five failed intubations (0.6%), two patients were managed via bag valve mask and orophayrngeal airway, and one patient via supraglottic airway. No surgical airways or cardiac arrests occurred. The most common clinical indication for RSI was traumatic brain injury (50.5%), followed by non-traumatic intracranial pathology (9.5%). A total of 226 (29.1%) patients had a pre-induction GCS≥12. Conclusion: A very high RSI procedural success rate was observed across the study period. This supports the growing recognition that appropriately-trained paramedicsclinicians can perform RSI safely in the pre-hospital environment. Conflict of interest: None declared. Funding: None declared.